Factors affecting maternal health care seeking behaviour in northeast states, India: evidence from district level household survey-4 (2012-2013) - Singh, Kh. Jitenkumar; Grover, Kanika (International Journal of Research in Medical Sciences, 2016)
Background: In context of reducing maternal mortality ratio, Government of India has implemented various programs and public health facility centres in order to provide quality services at the time of delivery. In this paper, we assessed the factors for home, private and public health facility sector utilization of delivery care in Northeast state, India. District Level Household Survey fourth round was used to carried out analysis and data was extracted for the childbirth during the last five years preceding the survey. Methods: The outcome variable was categorical, thus multinomial logistic regression was used to assess the factors of each variable independently on the predictor variables. To check the collinearity, variance inflation factor (VIF) was computed for all variables prior to inclusion of multilevel logistic regression. Results: This shows that equal proportion of delivery was conducted at home (45%) and public health facility (45.2%) in comparison with private health facility (9.8%). For the choice set of public versus home, women with higher number of living children, wealth quintile and living in urban areas were associated with greater odds of delivering at public health facility centres. Conclusions: The initiative programs can be implemented by the government by sending trained professionals with supplements required by pregnant women at each and every district in order to promote maternal health and recruit more interdisciplinary team, which will be responsible for maintaining women and infant health, and thus providing appropriate medical advice.